A qualitative study on the current status and problems of pharmacists in home healthcare from the viewpoint of care managers in medically underpopulated areas in Japan - Yuji Nakagawa; Hideo Kato; Takuya Iwamoto (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Unlike in urban areas, community healthcare in medically underpopulated areas in Japan is constantly challenged because of the uncertainty in effectively using the limited resources. However, no study has focused on human resources or identified the actual state of pharmacists’ support in the community. Therefore, our study identified the actual status and problems of pharmacists involved in home medical care in medically underpopulated areas and discussed the roles required of pharmacists and specific methods of support. Methods The content of semi-structured interviews with care managers involved in home healthcare in Misugi town, Tsu City, between November 10, 2023 and March 13, 2024, was analyzed qualitatively using the grounded theory approach. Results Five care managers participated in the study. Semi-structured interviews on the actual situation and challenges faced by pharmacists indicated that the following roles were required for pharmacists: as in other regions, it was observed that elderly people with dementia and those living alone managed their medicines, adjusted leftover medicines, collaborated with other professions, bridged with physicians, checked medication status through frequent visits, and adhered to internal medication regimens. Issues related to the characteristics of depopulated areas were identified including human resources, limitations of healthcare resources, economic burden, limits on the number of visits by pharmacists. As a characteristic of communities with no pharmacies and only in-hospital prescribing, pharmacists were expected by care managers to manage the problems caused by in-hospital prescribing. Conclusions Our findings suggest that pharmacists should ensure the number of visits and collaborate with attending physicians, visiting nurses, and care managers to conduct drug management for patients with dementia and older adults living alone. Community healthcare specialists and those involved in the healthcare planning system can also utilize these findings while planning home healthcare to those who live in medically underpopulated areas in Japan.